Attorney Stories of Environmental Crime: Harms, Agents, and Ideal Cases - Ningard, Holly (2018)
We know and make sense of the world through stories. As such, stories shape our expectations for the future, and subsequently our behaviors. This dissertation project investigates attorney stories of environmental crime, contributing to a growing body of literature in both narrative criminology and green cultural criminology. I uncovered three stories of environmental crime commonly told by 14 attorneys, involved in environmental practice, with whom I conducted qualitative interviews: 1) low-hanging fruit stories, which involve a direct harm to the environment perpetrated recklessly or negligently by an individual perpetrator, 2) stories of the state as an agent of harm, where the harm focused on is perpetrated by overbearing environmental regulations and regulatory agencies, and 3) stories which describe a shift to agentless environmental harms, where we are all responsible for the perpetration of complex environmental issues. The aforementioned stories largely omit victims and obscure harms. They vilify the state and extant remedies. By holding everyone accountable for perpetuating the complex environmental harms we face today, it allows no one in particular to be held accountable. In these ways, they uphold a culture that lets complex but pressing harms continue to be done with impunity. I hope my inquiry can help to construct new stories of resistance